Problem of Periodization and Some Aspects of the Late Work of F. Bret Hart - A. B. Tanaseichuk; O. Yu. Osmukhina (Научный диалог, 2021)
The article is devoted to the discussion of the problem of periodization and the study of the features of the late stage of the work of the outstanding American prose writer Francis Bret Hart (1836—1902). The relevance of the article is due to the need to build a coherent and consistent history of the development of American literature at the turn of the 19th and 20th centuries, an important part of which is the writer’s prose heritage. The authors comprehend Western (J. Stewart, G. Scharnhorst, A. Nissen and others) and domestic (A. V. Vaschenko, L. P. Grossman, P. E. Schegolev, A. I. Startsev, V. A. Libman, E. Yu. Rogonova, A. B. Tanaseichuk) studies on biography and various aspects of the prose writer. The scientific novelty of the work lies in the fact that for the first time in American studies a gap in the reception of F. Bret Hart's work was filled (the absence of clear criteria for periodization); the tradition of a disdainful attitude to the European period of his work, established in American literary criticism, is refuted, in particular, it is proved that in the stories and novels of the 1880s and 1890s Bret Hart boldly goes beyond the usual themes and images: the “Californian theme”, traditional for his early prose, takes on a new dimension — in the aspect of understanding national and gender psychology (“Maruga”); amorous and melodramatic collisions are combined with an appeal to science fiction (“The Secret of the Hacienda”).